Jamaica : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Jamaica. (IMF Staff Country Reports; Country Report, 2008)
Economic growth variability is low in Jamaica, with deviations driven more by weather than by external conditions. External developments do, however, have large financial implications for Jamaica. Developments in Jamaica can, in turn, have a significant influence in the wider Caribbean. A recent political transition provides an opportunity to reinvigorate reforms but success will require consensus across the political divide. Economic growth has slowed to 1 percent in FY2007/08 (ending in March), although inflation has surged to 18 percent in recent months.